2014
DOI: 10.1111/hex.12258
|View full text |Cite
|
Sign up to set email alerts
|

Doctors’ perspectives of informed consent for non‐emergency surgical procedures: a qualitative interview study

Abstract: Background The need to involve patients more in decisions about their care, the ethical imperative and concerns about ligation and complaints has highlighted the issue of informed consent and how it is obtained. In order for a patient to make an informed decision about their treatment, they need appropriate discussion of the risks and benefits of the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 21 publications
2
45
0
Order By: Relevance
“…We conducted a brief literature review on the process of informed consent which revealed a lack of studies on the doctors' perspectives of the consent process. Even fewer studies [15,28,30] already conducted had expressed views about how the consent process was undertaken. This study was part of a bigger study and the interview schedule was piloted on 20 persons (n = 5 doctors).…”
Section: Participants Ethical Approval and Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…We conducted a brief literature review on the process of informed consent which revealed a lack of studies on the doctors' perspectives of the consent process. Even fewer studies [15,28,30] already conducted had expressed views about how the consent process was undertaken. This study was part of a bigger study and the interview schedule was piloted on 20 persons (n = 5 doctors).…”
Section: Participants Ethical Approval and Proceduresmentioning
confidence: 99%
“…In PNG if patient rights are violated, the only recourse is to approach the consumer courts. Prominent features of patients' rights, responsibilities and code of ethics [28] are given in Table 7 (adopted and amended).…”
Section: Laws About Informed Consentmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence, however, that professionals often view obtaining consent as a procedural formality. 1 If so, the process may fail to meet ethical and professional requirements. A recent landmark case has seen the law better match these guidelines, and now sets-out clear standards of communication required to prepare patients for treatment.…”
Section: Introductionmentioning
confidence: 99%